Representations and Restitutions of African Traditional Healing Systems - (:unkn) unknown (My University, 2002)
Volume entitled: Bodies and Politics. Healing Rituals in the Democratic South Africa, Co-ordinated by Véronique FAURE, co-edited by Arnold SHEPPERSON
Keywords: African Research